Understanding disability from a secondary data lens perspective: Evidence from consultations with members of the public with disabilities in the UK - Eirini-Christina Saloniki; William Lammons; Sarah Markham (PLoS ONE, 2025)
Disability is a multifaceted phenomenon, which complicates data collection about people with disabilities in surveys and censuses. A central issue is that the multiple underlying theoretical models about disability are seldomly made explicit yet strongly determine how data are collected and analysed by governments and organisations. It is crucial that such models together with other information about disability and its measurement are accessible and understood by everyone. This study comprised several UK survey searches for disability or disability-related questions and a series of consultations with members of the public with lived experience of disability to understand their perceptions of theoretical models of disability in survey questions. The findings highlighted the importance of continued involvement of people with lived experience in technical research activities. They further revealed that members of the public with lived experience can effectively become familiar with theoretical models of disability and how to analyse them in relation to survey questions subject to careful preparation, including practical examples.